Web-based illustrated history of Sibangkaja: A digital humanities approach - Adnyana, I Nyoman Widhi; Ariningsih, Kadek Ayu; Ardana, I Putu Dhiva Wira (Privietlab, 2025)
The fragility of local historical memory in Sibangkaja Village has become increasingly evident as oral traditions fade and social transformations accelerate under the pressures of urbanization and digital cultural penetration. This underscores the urgent need to reconstruct, document, and digitize ancestral narratives as part of community-based cultural heritage preservation efforts. This study aims to identify the structure and dynamics of Sibangkaja’s historical memory and explore the application of digital humanities in revitalizing local knowledge through web-based visual storytelling media. The research employed oral history interviews, participatory observation, an archival study of cultural records, and the transmediation of historical narratives into interactive visual formats. The findings reveal that Sibangkaja’s collective memory is deeply embedded in local cosmology, religious rituals, and kinship structures, while carrying moral values that connect humans to their ancestors and their lived environment. Digitizing memory through a web-based pictorial storytelling medium demonstrated expanded access to knowledge, enhanced engagement among younger generations, and the creation of intergenerational cultural collaboration spaces for the elderly. This study proposes a community-based digital-archiving model that integrates local epistemology, digital technology, and visual-narrative approaches. Its primary contribution lies in advancing digital humanities in the context of Indonesian customary villages while strengthening the discourse on knowledge decolonization and cultural pedagogy in the digital transformation era.